KEBIJAKAN PENGELOLAAN SARANA DAN PRASARANA DI SMP ISLAM AL-ISTIQOMAH KARAWANG: TINJAUAN ASPEK PERENCANAAN, PENGADAAN, INVENTARISASI, PEMANFAATAN, PEMELIHARAAN, DAN EVALUASI - Nabilah Choirunnisa; Ajat Rukajat; Wahidin Wahidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the policy of managing facilities and infrastructure at SMP Islam Al-Istiqomah Karawang from the aspects of planning, procurement, inventory, utilization, maintenance, and evaluation. A descriptive qualitative method with a case study approach was used. Data were collected through semi-structured interviews, direct observation, and inventory document review. The informants included the principal, vice principal for facilities, three teachers, and three students. The results show that: (1) Planning is conducted through participatory needs identification with priority scales based on actual facility conditions, though not yet supported by written blueprint documents; (2) Procurement relies on BOS funds and foundation resources with clear procedures but constrained by budget limitations; (3) Inventory is managed manually through secondary inventory documents with annual updates; (4) Facility utilization applies internal rules including restrictions on Smart TV use for learning only; (5) Maintenance is conducted through biannual inspections, but repair delays occur due to budget limitations; (6) Evaluation is carried out through quarterly coordination meetings. Overall, the facilities management policy is functioning but requires strengthening in written documentation and maintenance consistency.